RSM and fuzzy modeling approach for optimization of extraction of antioxidant compounds from Asparagus racemosus roots. Issue 1 (28th February 2023) - Singh, Akshay K.; Kumar, Vivek; Singh, Karunakar; Fatima, Sumaiya
Abstract: This research work was carried out to explore the influence of extraction methods on the extraction of antioxidant from Asparagus racemosus roots. The microwave‐assisted extraction (MAE) method was more efficient as compared with continuous shaking extraction (CSE) method in terms of total phenolic content (TPC), total flavonoids content (TFC), 2, 2‐diphenyl‐1‐picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and total antioxidant capacity (TAC) content in the ethanolic extract of A. racemosus roots. Box–Behnken experimental design of response surface methodology (RSM) was used to optimize MAE method for three process parameters viz. solvent concentration (SC: 40%–90% v/v), extraction time (ET: 10–30 min), and microwave power (MP: 360–720 W). Model fitness of the experimental data was determined by multiple regression analysis and analysis of variance. The optimum targeted parameters were obtained as 65% v/v SC, 23 min ET, and 560 W MP, and the corresponding responses TPC, TFC, DPPH, FRAP, and TAC were found to be 9.377 mg GAE/g, 177.03 mg QE/g, 65.70%, 193.35 mM Fe +2 /g, and 496.97 mg AAE/g with a desirability of 0.95. Fuzzy modeling with Mamdani‐type fuzzy inference was also utilized to obtain the most optimal conditions for specified process parameters and responses under the set of rules for process parameters and responses. The estimated results of responses by both RSM and fuzzy model showed good agreement with the experimental values. Abstract : Microwave‐assisted extraction (MAE) method was found best for the extraction of antioxidant from Asparagus racemosus roots powder as compared with continuous shaking extraction (CSE) method. The optimum targeted conditions for MAE extraction were determined using response surface methodology (RSM) and found as 65% v/v solvent concentration (SC), 23 min extraction time (ET), and 560 W microwave power (MP). Under these optimum conditions, the responses, total phenolic content, total flavonoids content, 2, 2‐diphenyl‐1‐picrylhydrazyl, ferric reducing antioxidant power, and total antioxidant capacity were 9.377 mg GAE/g, 177.05 mg RE/g, 65.70%, 193.40 mg Fe +2 /g and 496.97 mg AAE/g. Fuzzy modeling through Mamdani‐type fuzzy inference was also determined the optimum process conditions for the extraction of antioxidant from A. racemosus roots powder. The predicted value of responses by both RSM and fuzzy model showed good agreement with the experimental values.